Infant gut microbiota modulation by human milk disaccharides in humanized microbiome mice. (1st January 2021) - Rubio-Del-Campo, Antonio; Gozalbo-Rovira, Roberto; Moya-Gonzálvez, Eva M.; Alberola, Juan; Rodríguez-Díaz, Jesús; Yebra, María J.
ABSTRACT: Human milk glycans present a unique diversity of structures that suggest different mechanisms by which they may affect the infant microbiome development. A humanized mouse model generated by infant fecal transplantation was utilized here to evaluate the impact of fucosyl-α1, 3-GlcNAc (3FN), fucosyl-α1, 6-GlcNAc, lacto- N -biose (LNB) and galacto- N -biose on the fecal microbiota and host–microbiota interactions. 16S rRNA amplicon sequencing showed that certain bacterial genera significantly increased ( Ruminococcus and Oscillospira ) or decreased ( Eubacterium and Clostridium ) in all disaccharide-supplemented groups. Interestingly, cluster analysis differentiates the consumption of fucosyl-oligosaccharides from galactosyl-oligosaccharides, highlighting the disappearance of Akkermansia genus in both fucosyl-oligosaccharides. An increment of the relative abundance of Coprococcus genus was only observed with 3FN. As well, LNB significantly increased the relative abundance of Bifidobacterium, whereas the absolute levels of this genus, as measured by quantitative real-time PCR, did not significantly increase. OTUs corresponding to the species Bifidobacterium longum, Bifidobacterium adolescentis and Ruminococcus gnavus were not present in the control after the 3-week intervention, but were shared among the donor and specific disaccharide groups, indicating that their survival is dependent on disaccharide supplementation. The 3FN-feeding group showed increased levels of butyrate and acetate in the colon, and decreased levels of serum HDL-cholesterol. 3FN also down-regulated the pro-inflammatory cytokine TNF-α and up-regulated the anti-inflammatory cytokines IL-10 and IL-13, and the Toll-like receptor 2 in the large intestine tissue. The present study revealed that the four disaccharides show efficacy in producing beneficial compositional shifts of the gut microbiota and in addition, the 3FN demonstrated physiological and immunomodulatory roles.